Perubahan Kandungan Protein Kasar dan Bahan pada Kacang Kedelai yang difermentasi dengan Probiotik Heryaki cair - Ega Putri Rahayu; Deny Saefulhadjar; Hery Supratman (Program Studi Peternakan, Universitas Padjadjaran PSDKU Pangandaran, 2023)
The purpose of this research was to figure out of the best effect of crude protein and dry matter use liquid heryaki probiotic dosage in soybeans fermented. The parameters observed were the content of changes in crude protein and dry matter. The research method used was an experimental method with a completely randomized design. There were three threatments of soybean fermented, namely P1= 3% probiotic, P2= 6% probiotics, P3= 9% probiotic. Performed 6 repetitions of each treatment. Data analysis used analysis of variance (ANOVA). The result showed the difference probiotic dosage fermented process had no sign on effect the changes of crude protein and dry matter.. Keywords: Soybean, liquid Heryaki probiotic,, fermentation, dry matter, crude protein